Incidence of metabolic bone disease in rheumatoid arthritis and osteoarthritis. Issue 3 (June 1984) - Ng, K C; Revell, P A; Beer, M; Boucher, B J; Cohen, R D; Currey, H L
Abstract : Bone biopsy specimens from the iliac crest were obtained during surgical operations from 45 patients with rheumatoid arthritis (RA) and 41 with osteoarthritis (OA). Control material was obtained from 20 cases of sudden death due to cardiovascular disease. By both conventional histology and image analysis techniques about a quarter of all patients showed some osteoporosis. This was equally common among the OA and RA patients. It was more common among those with transparent skin and those taking corticosteroids. The only case showing mild osteomalacia suffered from OA. No gross differences were apparent between the groups in relation to plasma biochemical studies, diet, or exposure to sunlight. These results are in striking contrast to the high incidence of osteomalacia in RA reported from the west of England; moreover they do not confirm reports of hypercalcaemia among rheumatoid subjects. We conclude that the differences regarding osteomalacia are due to selection of cases. We find no evidence that osteomalacia is specifically associated with RA.